Genome-wide association study for Streptococcus iniae in Nile tilapia (Oreochromis niloticus) identifies a significant QTL for disease resistance - Vela-Avitúa, Sergio; LaFrentz, Benjamin R.; Lozano, Carlos A.; Shoemaker, Craig A.; Ospina-Arango, Jose Fernando; Beck, Benjamin H.; Rye, Morten (Frontiers in Genetics, 2023)
Streptococcus iniae is a problematic gram-positive bacterium negatively affecting Nile tilapia (Oreochromis niloticus), one of the main aquacultural species produced worldwide. The aim of this study was to identify genetic architecture of survival to S. iniae and to identify single nucleotide polymorphism (SNPs) linked to quantitative trait loci (QTL) related to survival to S. iniae challenge. With this purpose, fish from the Spring Genetics breeding program were sent to a controlled S. iniae challenge test where phenotypes were scored as dead for fish that died during the duration of the test and survivors for the fish alive at the termination of the test. Additionally fin-clip samples from all fish in the test were collected for DNA extraction. Out of 1904 fish in the challenge test, tissue samples of 321 fish were sent for genotyping using double digest restriction site associated DNA sequencing (ddRADseq). After quality control and filtering, 9085 SNPs were used to perform a genome wide association study (GWAS). A significant signal in LG8 was observed indicating association with survival to S. iniae challenge, with SNPs explaining from 12% to up 26% of the genetic variance. To prove the usefulness of marker assisted selection (MAS) to selectively breed fish for survival to S. iniae, offspring of breeding candidates classified as “resistant” and “susceptible” based on haplotypes of the four most significant markers were sent to a controlled S. iniae challenge test. At the end of the test, the differences in mortality between the two groups were strikingly different with a final cumulative percent mortality of nearly 0% and 73% for offspring from “resistant” and “susceptible” parents, respectively. These results demonstrate that selection for disease resistance to S. iniae is feasible using MAS.